Plantio direto e decomposição de restos culturais em diferentes sistemas de cultivos - Nunes, Helber Véras (2006)
The studies were driven in the Experimental Station the State Company of Agricultural Research of Paraíba - EMEPA - PB, mucicipality to Alagoinha - PB, aiming at to acquire information on the productive behavior of maize plants, the physiologic quality of its seeds and decomposition of cultural rests, identifying a more advantageous system, more vigorous seeds and more persistent cultural rests in direct sowing. The first trial followed experimental drawing in random block designs, with subdivided plots and three replications. The main plots (5x16 m) consisted of three systems of cultivations {maize, (Zea mays) cultivar BR-106 in monosowing, maize + guandu bean (Cajanus cajan) and maize + faba bean (Phaseolus lunatus)}, sowed in the beginning of the rainy period, and the subplots (5x4 m) of two doses of mineral manuring {0 kg/ha and 825 kg/ha of the formulation 90-60-45}, were applied in strips. Green manuring (absence and presence), assuming the form of black mucuna (Styzolobium aterrinum), was sowed every year around eighty-five days after the sowing of the cultivations systems, was accomplished in strips in the blocks (sub-blocks with 15x8 m). Spacing used in maize was 1,0 x 0,20 m (50.000 plants/ha), guandu bean was planted inserted among alternate maize rows, sowed in spaced ditches of 0,50 m (10.000 plants/ha), faba bean was sowed in alternate maize rows in spaced ditches of 1,0 m, two plants for ditch (10.000 plants/ha) while black mucuna was sowed inserted among maize rows, eighty-five days after the systems sowing, in spaced ditches of 0,25 m (40.000 plants/ha). For the second trial, after the crop, samples of maize seeds were conditioned in packings of polyethylene, maintained through the period of three months in cold and dry camera. Then they were led to the Seeds Analysis Laboratory, from the Center of Agrarian Sciences of the Federal University of Paraíba in Areia - PB in order to get physiologic quality evaluation, being submitted to the following tests: germination, first germination counting, electric conductivity, emergency of seedlings in sand, emergency speed index, dry mass of the aerial part of seedlings, cold with and without soil. Cultural rests of maize were used; braquiarian grass (Braquiaria decumben); faba bean; guandu bean and black mucuna, dry to the air and fractionated in small pieces (0,01 - 0,05 m). After that, they were conditioned in 20 x 30 cm nylon bags, with 1,0 mm2 mesh. Each nylon bag received 60 g of dry cultural rest, equivalent to 10 t/ha, distributed and fastened in the soil surface. Nitrogen, assuming the form of urea (1,07 g/bag), was diluted in water and applied immediately on the nylon bags (0 and 80 kg/ha), with a watering of 600 ml/bag, equivalent to a 10 mm rain. The nylon bags crop was accomplished in consecutive periods of 36 days. Material contained in each bag was clean, dry in a stove and weighted, evaluating this way the decomposition of the cultural rests. Along the experiment process, pluvial precipitation, air temperature, soil humidity and temperature to 2 cm depth were quantified. Taking the results into consideration, it was possible to conclude that: mineral manuring elevated grains income, soil covering, dry mass production, length and diameter of ear maize, plant and ear height and stem diameter of maize plants; the black mucuna sowed eighty-five days after the systems sowing of cultivations increased maize grains income and dry mass production; intercrop corn + faba bean emphasized faba bean as a second culture of economical value and maize + guandu did so for the largest dry mass production; the mineral fertilizer favored the viability and the maize seeds vigor; black mucuna, besides not having competed with the culture systems, favored the physiologic quality of maize seeds coming from intercropping and the intercropping maize + guandu bean favored the vigor the seed maize; decomposition of cultural rests was influenced by pluvial precipitation, soil humidity and temperature and air temperature, during the experimental period; nitrogened manuring promoted larger reduction in the cultural rests dry mass; the braquiarian grass and guandu bean cultural rests were the most resistant to decomposition, while the black mucuna ones presented an intermediate behavior, and the maize and faba bean cultural rests were the least resistant ones.